Intraspecific variation in the axial skeleton of Aetosauroides scagliai (Archosauria: Aetosauria) and its implications for the aetosaur diversity of the Late Triassic of Brazil - PAES-NETO,VOLTAIRE D. (2021)
Abstract Aetosauria represents a remarkable clade of armored pseudosuchians in which some of its oldest members are recovered from late Carnian units of Brazil. Three species are known: the mid-sized aetosaur Aetosauroides scagliai, which also occurs in Argentina, and two small-sized species, Aetobarbakinoides brasiliensis and Polesinesuchus aurelioi. We provide a detailed description and comparative analysis of the axial skeleton of Aetosauroides, identifying some diagnostic features as variable. These include the deep pocket pit lateral to the base of the neural spine, the presence of the infradiapophyseal laminae and the lateral fossa ventral to the neurocentral suture. These features are not found in smaller and immature Aetosauroides specimens, resembling the condition found in Polesinesuchus, which is based solely on a juvenile individual, as revealed by osteoderm microstructure analysis. As Polesinesuchus cannot be anatomically differentiated from other small individuals of Aetosauroides, we propose it as a junior synonym of Aetosauroides scagliai. Our results shrink the number of putative ‘dwarf’ aetosaurs, indicating that morphological variation related to ontogeny affects aetosaur taxonomy and phylogeny.